L'Église et l'État aux États-Unis: la langue et l'éducation - Hudon, Edward (Les Cahiers de droit, 1978)
In both Canada and the United States, the relationship between Church and State has caused problems which have had to be resolved by the courts on a case by case basis. In Canada, much more than in the United States, there have also been problems over the language question which also have had to be resolved by the courts. Indeed, in Canada the language issue can be considered to be the counterpart of the black versus white problem of the United States. In both Canada and the United States, the question is the protection of the rights of the minority, but the constitutional provisions of each that relate to these rights have a different approach. In Canada they take the form of permissions which are found in Sections 93 and 133 of the British North America Act. In the United States they are in the form of prohibitions found in the First and the Fourteenth Amendments to the Constitution of the United States. In Canada, the effect of the Constitutional provisions vary from Province to Province, depending on what the situation was in a Province at the time it became apart of the Dominion. In the United States, the Constitutional prohibitions apply to all of the States in the same manner. But whatever the nature of the Constitutional provision, in both countries there has not been a lack of cases. Moreover, in both countries a quick, easy solution to the problems presented will probably never be found. Meanwhile, about all that the courts of either country can do is to continue the case by case approach so that it will present a reasonably consistent pattern as new problems develop and passions erupt.